Lectures in Canadian Labour and Working-Class History - Committee on Canadian Labour History; Cherwinski, W. J. C. (Walter Joseph Carl); Kealey, Gregory S. (Past CCLH Publications, 1985)
In 1983 and 1984 the Canadian Studies Program of the Secretary of State funded four lecture series at Canadian universities on the history of the Canadian working class. This volume presents many of the lectures in a published version. Ranging from east to west and covering two centuries of Canadian labour history, the volume includes a selection of essays by some of Canada's leading social historians including Michael Cross, David Frank, Ross McCormack, Bryan Palmer and Joy Parr. Outstanding participants in the making of Canadian labour history Eugene Forsey and H. Landon Ladd have also contributed. Directed at a popular audience these fourteen lectures provide a major survey of Canada's labour past. --Publisher's description
Keywords: Canada; History; Labor; Labor Unions; Labor movement; Working class